2008
DOI: 10.1111/j.1530-0277.2007.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of the ε2 Allele of Apoe Gene to Hypertriglyceridemia and to Early‐Onset Alcoholic Cirrhosis

Abstract: This study shows the association of hypertriglyceridemia and APOE allele with the early onset of alcoholic liver cirrhosis, and the interaction between environmental factors, such as duration of alcohol abuse and amount of alcohol intake, and genetic factors (APOE*2 allele) on the hypertriglyceridemic process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…[23] In regards to age, ALD was prevalent mainly in relatively young male adults, as observed in previous studies that showed that patients with ALD and LC were younger as compared to other populations. [24] However, in this study the patients with NASH were the youngest. In fact, a higher BMI, as well as IR and diabetes were more prevalent in this group.…”
Section: Discussionmentioning
confidence: 70%
“…[23] In regards to age, ALD was prevalent mainly in relatively young male adults, as observed in previous studies that showed that patients with ALD and LC were younger as compared to other populations. [24] However, in this study the patients with NASH were the youngest. In fact, a higher BMI, as well as IR and diabetes were more prevalent in this group.…”
Section: Discussionmentioning
confidence: 70%
“…In an effort to better understand the bases underlying this nosological entity, a variety of studies describing possible molecular and pathophysiological factors involved have been accomplished (Bastidas-Ramı´rez et al, 2002;Gordillo-Bastidas et al, 2010;Herna´ndez-Nazara´et al, 2008;Nun˜o-Gonza´lez et al, 2005). Ethnicity influence over differential susceptibility to alcoholic liver disease has widely been determined (Douds et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, determination of genotype and allele distribution of other CYP2E1 variant forms in HUI, may be of importance. Individuals included in this study were clinically healthy people representing the general population; notwithstanding, liver function tests and lipid profile were determined to evaluate possible incipient alterations associated to genotype, as these parameters could be indicative of liver dysfunction (Herna´ndez-Nazara´et al, 2008). Mean hepatic function values were normal and not statistically different in HUI and MES.…”
Section: Discussionmentioning
confidence: 99%
“…Although lack of significant genotype association, HUI presented a better lipid profile than MES. Recently, the absence of the Apo e2 allele and high prevalence (28%) of the Apo e4 allele have been documented in HUI (Aceves et al, 2006), which are related to hypertriglyceridemia and latest onset of liver cirrhosis, respectively (Herna´ndez-Nazara´et al, 2008). Besides, HUI are habituated to a low fat, maize-rich diet, and high physical activity (Aceves et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation